Hybrid Online Dispute Resolution for Small-Value E-Commerce Consumer Disputes: Integrating Inclusive Legal Thought and Maqāṣid al-Sharīa - Musataklima Musataklima; Khairul Umam; Mahbub Ainur Rofiq; Abdul Kadir; Dwi Fidhayanti (Justicia Islamica, 2026)
The growth of e-commerce has increased transaction volumes while also giving rise to small-value consumer disputes that cannot yet be effectively resolved through conventional mechanisms. This study aims to analyze the need to implement Hybrid Online Dispute Resolution (ODR) to resolve small-scale e-commerce consumer disputes and to examine its normative foundations from the perspective of Indonesia’s inclusive legal thought and maqāṣid al-sharīa. The study employs a doctrinal legal method, drawing on legislative and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through a literature review and then qualitatively analyzed using prescriptive analysis techniques through systematic interpretation and legal construction. The results indicate that Hybrid ODR holds philosophical urgency as an instrument that broadens access to justice, accelerates dispute resolution, and reduces the costs of case resolution. From a sociological perspective, this model addresses the rising number of consumer disputes in e-commerce and the limited capacity of the Consumer Dispute Resolution Agency (BPSK). From a legal perspective, Hybrid ODR has the potential to strengthen legal certainty and enhance the effectiveness of consumer protection by integrating online and offline mechanisms. From the perspective of inclusive law, this model derives its legitimacy from nonlinear postulates, the religious character of law that aligns with maqāṣid al-sharīa, particularly ḥifẓ al-māl, and the affirmative action postulate, which provides greater protection for consumers as a vulnerable group. This study contributes by proposing Hybrid ODR as an adaptive, inclusive, and context-sensitive dispute-resolution model to strengthen Indonesia's consumer protection system within its e-commerce ecosystem.